Blurred Lines: The Ethics and Policy of Greenhouse Gas Removal at Scale - Cox, Emily M.; Pidgeon, Nick; Spence, Elspeth; Thomas, Gareth (Frontiers in Environmental Science, 2018)
The topic of Greenhouse Gas Removal (GGR) for climate geoengineering is becoming increasingly salient following the IPCC’s 5th Assessment Report and the Paris Agreement. GGR is thought of as a separate category to mitigation techniques such as low-carbon supply or demand reduction, yet multiple social, ethical and acceptability concerns cut across categories. We propose moving beyond classifying climate strategies as a set of discrete categories (which may implicitly homogenise diverse technologies), towards a prioritisation of questions of scale of both technology and decision-making in the examination of social and ethical risks. This is not just a theoretical issue: important questions for policy, governance and finance are raised, for instance over the future inclusion of GGR in carbon markets. We argue that the conclusions drawn about how best to categorise, govern and incentivise any strategy will depend on the framing used, because different framings could lead to very different policy recommendations being drawn. Because of this, a robust approach to developing, governing and financing GGR should pay attention first to urgent concerns regarding democracy, justice and acceptability.